Supported Cu-ZnO / long afterglow catalyst as well as preparation method and application thereof
By loading Cu-ZnO active components on long afterglow materials, the problems of catalyst deactivation and low CO2 reduction efficiency in the CO2 hydrogenation reaction of existing photocatalysts are solved, and the efficient CO2 hydrogenation reaction performance is achieved, and the CO generation rate is significantly improved.
Patent Information
- Application Number
- CN202411957295.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
In the CO2 hydrogenation reaction, existing photocatalysts have problems such as catalyst deactivation, high energy consumption and low CO2 reduction efficiency.
By loading Cu-ZnO active components on long afterglow materials, specific preparation methods are used to regulate the interaction between the active components and the carrier, forming more active centers and improving the CO2 hydrogenation reaction performance.
Under the photothermal synergistic catalytic conditions, the catalytic performance of Cu-ZnO/long afterglow catalyst on CO2 hydrogenation reaction is achieved, and the CO generation rate is increased by 6.6 times while maintaining high selectivity.
Smart Images

Figure CN119746869A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalyst materials, and in particular to a supported Cu-ZnO / long afterglow catalyst and a preparation method and application thereof. Background Art
[0002] With the increase of population and the wider range of human activities, the concentration of CO2 in the global atmosphere is increasing day by day. The greenhouse effect that follows has led to global warming and some severe environmental problems. Therefore, the reduction of CO2 emissions and the rational planning and utilization are particularly important.
[0003] Photothermal catalytic CO2 hydrogenation is a new method to achieve zero-pollution carbon conversion with high efficiency, because hydrogen as one of the reactants has the advantages of low cost and low carbon footprint. The process of catalytic reduction of CO2 hydrogenation can not only realize the recycling of carbon resources to obtain carbon products with high application value, but also effectively reduce the high concentration of CO2 in the atmosphere. However, as an extremely stable molecule, CO2 requires a large reaction energy barrier to be overcome in order to convert it into carbon-based products. At the same time, the reaction conditions of CO2 hydrogenation are relatively harsh, and the reaction usually requires feeding under high temperature and high pressure, which can easily lead to catalyst sintering and deactivation.
[0004] In the field of photocatalytic reduction of CO2, traditional catalytic materials include TiO2, CdS, ZnGa2O4 and Zn2GeO4. Due to factors such as high recombination probability of photogenerated electron-hole pairs, low visible light energy utilization, and weak CO2 adsorption capacity, the catalytic efficiency is limited, which seriously restricts the large-scale application of this technology.
[0005] Cu-Zn-based catalysts are the most widely studied catalysts in the reverse water gas shift reaction (RWGS), which is an endothermic process that helps produce CO at high temperatures. Although commercially available Cu-ZnO-based catalysts show good conversion and selectivity in CO2 hydrogenation reactions, they are prone to sintering and deactivation due to their poor thermal stability.
[0006] In addition, due to the inherent complexity of the CO2 hydrogenation reaction mechanism, and the existence of competing reactions and unfavorable kinetic and thermodynamic factors, the catalyst's CO2 conversion rate and product selectivity are not high. The product of CO2 hydrogenation photothermal catalytic reduction is mostly methane, and research on the product CO is not comprehensive. However, from the perspective of application prospects, the influence of CO is far greater than that of methane. Therefore, how to improve CO to become a highly active and highly selective product in the CO2 hydrogenation reaction is a major problem. Summary of the invention
[0007] The purpose of the present invention is to provide a supported Cu-ZnO / long afterglow catalyst and a preparation method and application thereof.
[0008] In order to solve the problems existing in the prior art, the technical solution adopted by the present invention is:
[0009] In a first aspect, the present invention provides a supported Cu-ZnO / long afterglow catalyst, which uses a long afterglow material as a carrier and loads a Cu-ZnO active component on the surface of the long afterglow material by an impregnation method.
[0010] Preferably, the long afterglow material is Sr2MgSi2O7:Eu 2+ ,Dy 3+ .
[0011] Furthermore, the raw materials for preparing the active component are soluble copper salt and soluble zinc salt, and the molar ratio of Cu to Zn is 1-9:1, preferably 2.25:1.
[0012] Furthermore, the molar ratio of the active component Cu to Si in the long afterglow material is 0.3-1.8:1, preferably 0.6:1.
[0013] Preferably, the soluble copper salt is Cu(NO3)2, and the soluble zinc salt is Zn(NO3)2. Using Cu(NO3)2 and Zn(NO3)2 as raw materials for preparation has good structural performance advantages, strong controllability and high safety.
[0014] In a second aspect, the present invention provides a method for preparing the supported Cu-ZnO / long afterglow catalyst described in the first aspect, comprising the following steps:
[0015] S1: dissolving soluble copper salt and soluble zinc salt in anhydrous ethanol, stirring well to obtain solution A;
[0016] S2: Add the long afterglow material to solution A and continue stirring to obtain solution B;
[0017] S3: dissolving oxalic acid in anhydrous ethanol and stirring evenly to obtain solution C; dissolving oxalic acid in anhydrous ethanol can provide a relatively stable reaction environment, making the catalyst preparation process more controllable.
[0018] S4: Solution C is slowly and evenly added dropwise to solution B. After the addition is completed, stirring is continued for 0.5-6 hours at room temperature to obtain a gel precipitate. After aging at room temperature, the product is centrifuged and washed with anhydrous ethanol for 2-3 times. In this step, since solution C is added slowly and evenly, the metal ions can be evenly precipitated, the size and morphology of the precipitated particles can be controlled, the specific surface area of the catalyst and the exposure degree of the active sites can be increased, and the catalytic performance can be improved.
[0019] S5: Place in a drying oven at 80-120°C and dry for 8-24h, grind the dried catalyst solid into powder, and then roast in a muffle furnace at 300-500°C for 0.5-5h; the drying temperature and drying time in this step can ensure that the water in the material is completely removed; the roasting temperature and time in this step can effectively ensure that the nitrate is slowly and sufficiently decomposed into CuO, ZnO and NO2, and the metal oxides CuO and ZnO are left after the gas volatilizes.
[0020] S6: Reduce in a tube furnace at 300-500° C. for 1-3 h under a 10% H2-N2 atmosphere to obtain a supported Cu-ZnO / long afterglow catalyst.
[0021] Furthermore, in step S1, the molar ratio of Cu to anhydrous ethanol is 0.01-0.2:1, preferably 0.0175:1; in step S3, the molar ratio of oxalic acid to anhydrous ethanol is 0.01-0.2:1, preferably 0.03:1.
[0022] Furthermore, the molar ratio of Cu to oxalic acid is 0.1-5:1, preferably 0.6:1.
[0023] In a third aspect, the present invention provides the use of the catalyst described in the first aspect in the preparation of CO by photothermal catalytic reduction of CO2 hydrogenation.
[0024] Furthermore, the CO2 hydrogenation photothermal catalytic reduction to prepare CO is carried out in an intermittent reactor, H2 and CO2 are introduced into the intermittent reactor in a ratio of 3:1 to a pressure of 0.5-4MPa, and the amount of the supported Cu-ZnO / long afterglow catalyst used is 0.05-0.2g.
[0025] The advantages and beneficial effects of the present invention are:
[0026] The present invention adopts a specific preparation method to synthesize the Cu-ZnO / long afterglow catalyst, combines the Cu-ZnO active component with the long afterglow material, and regulates the interaction between the active component and the carrier by changing the ratio of Cu-ZnO to the long afterglow, so as to form more active centers and improve the CO2 hydrogenation reaction performance.
[0027] The Cu-ZnO / long afterglow catalyst synthesized by the present invention uses a photothermal synergistic catalytic method to hydrogenate and reduce CO2 to prepare CO, which can not only reduce the catalyst deactivation and energy consumption caused by the harsh reaction conditions of traditional thermal catalysis, but also solve the problems of CO2 reduction being difficult to achieve due to slow kinetics in traditional photocatalysis, and can greatly improve the catalytic performance of the Cu-ZnO / long afterglow catalyst for CO2 hydrogenation reaction. The present invention can continuously carry out photothermal catalytic reaction for 4 hours without the aid of external light sources, while maintaining a high selectivity for CO, and increasing the CO generation rate by 6.6 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 XRD spectra of CZ, 0.6CZ / LI, 0.6CZ / LP and L;
[0029] Figure 2 N2 physical adsorption-desorption isotherms and pore size partition curves of different catalysts;
[0030] Figure 3 is the UV-vis absorption spectra of different catalysts;
[0031] Figure 4 The Tauc plots of four catalysts, CZ, L, 0.6CZ / LI and 0.6CZ / LP, where a is CZ, b is L, c is 0.6CZ / LI, and d is 0.6CZ / LP;
[0032] Figure 5 XPS fine spectra of Cu in three catalysts: CZ, 0.6CZ / LI and 0.6CZ / LP; a is the XPS spectrum of Cu 2p; b is the Cu LMM Auger spectrum;
[0033] Figure 6 The XPS fine spectra of Zn and O1s in the three catalysts CZ, 0.6CZ / LI and 0.6CZ / LP, where a is the 2p spectrum of Zn; b is the XPS spectrum of O1s;
[0034] Figure 7 The XPS fine spectra of VB of three catalysts: CZ, 0.6CZ / LI and 0.6CZ / LP;
[0035] Figure 8 H2-TPR diagrams of four catalysts: CZ, L, 0.6CZ / LI and 0.6CZ / LP;
[0036] Fig. 9 CO2-TPD diagrams of four catalysts: CZ, L, 0.6CZ / LI and 0.6CZ / LP;
[0037] Fig.10 The selectivity performance diagram of the product under different experimental conditions; a is the selectivity of the product under different pressures; b is the selectivity of the product under different temperatures;
[0038] Fig.11 is the catalytic performance of different catalysts in the reaction; where a is the selectivity of the product CO; b is the conversion rate of CO2;
[0039] Fig.12 It is the Arrhenius plot of CZ and 0.6CZ / LI in the reaction;
[0040] Fig.13 is the CO2 conversion rate of CZ and 0.6CZ / LI at different temperatures;
[0041] Fig.14 This is a stability test of the 0.6CZ / LI catalyst. DETAILED DESCRIPTION
[0042] The following will be combined with the drawings in the embodiments of the present application to clearly describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application belong to the scope of protection of this application.
[0043] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0044] Example 1
[0045] This embodiment provides a supported Cu-ZnO / long afterglow catalyst, and its preparation method is as follows:
[0046] S1: Dissolve 5.44 g of Cu(NO3)2·3H2O and 2.97 g of Zn(NO3)2·6H2O in 75 mL of anhydrous ethanol and stir well to obtain solution A;
[0047] S2: Add 2.22 g of Sr2MgSi2O7:Eu to solution A. 2+ ,Dy 3+ (SMSOED), continue stirring to obtain solution B;
[0048] S3: Dissolve 5.04 g of oxalic acid H2C2O4·2H2O in 75 mL of anhydrous ethanol and stir to obtain solution C;
[0049] S4: Solution C is slowly and evenly added dropwise to solution B. After the addition is completed, stirring is continued for 4 hours at room temperature of 25°C to obtain a gel precipitate. After aging at room temperature, the product is centrifuged and washed twice with anhydrous ethanol;
[0050] S5: Dry in a drying oven at 105°C for 12 hours, grind the dried catalyst solid into powder, and then calcine in a muffle furnace at 370°C for 1 hour;
[0051] S6: Finally, the catalyst was reduced at 500°C for 2h in a tubular furnace under a 10% (v / v) H2-N2 atmosphere to obtain a supported Cu-ZnO / long afterglow catalyst. The ICP test showed that the molar ratio of Cu to Si in this embodiment was 0.6, recorded as 0.6CZ / LI.
[0052] Example 2
[0053] This embodiment provides a supported Cu-ZnO / long afterglow catalyst. The difference between this embodiment and embodiment 1 is only that the loading amount of the long afterglow is different. In step S2 of this embodiment, 4.44 g of Sr2MgSi2O7:Eu 2+ ,Dy 3 + , the rest are the same as in Example 1, and are obtained through ICP testing. In this example, the molar ratio of Cu to Si is 0.3, which is recorded as 0.3CZ / LI.
[0054] Example 3
[0055] This embodiment provides a supported Cu-ZnO / long afterglow catalyst. The difference between this embodiment and embodiment 1 is only that the loading amount of the long afterglow is different. In step S2 of this embodiment, 1.11 g of Sr2MgSi2O7:Eu2O7 is added to solution A. 2+ ,Dy 3 + , the rest are the same as in Example 1, and are obtained through ICP testing. In this example, the molar ratio of Cu to Si is 1.2, which is recorded as 1.2CZ / LI.
[0056] Example 4
[0057] This embodiment provides a supported Cu-ZnO / long afterglow catalyst. The difference between this embodiment and embodiment 1 is only that the loading amount of the long afterglow is different. In step S2 of this embodiment, 0.74 g of Sr2MgSi2O7:Eu 2+ ,Dy 3 + , the rest are the same as in Example 1, and are obtained through ICP test. In this example, the molar ratio of Cu to Si is 1.8, which is recorded as 1.8CZ / LI.
[0058] Example 5
[0059] This embodiment provides a supported Cu-ZnO / long afterglow catalyst, and its preparation method is as follows:
[0060] S1: Preparation of Cu-ZnO oxide particles:
[0061] ① Dissolve 5.44 g of Cu(NO3)2·3H2O and 2.97 g of Zn(NO3)2·6H2O in 75 mL of anhydrous ethanol and stir to obtain solution A;
[0062] ② Dissolve 5.04 g of H2C2O4·2H2O in 75 mL of anhydrous ethanol and stir to obtain solution C;
[0063] ③Slowly and evenly add solution C to solution A. After the addition is completed, stir continuously for 4 hours at room temperature 25°C. After aging at room temperature, centrifuge the product and wash it twice with anhydrous ethanol.
[0064] ④ Place in a drying oven at 105°C and dry for 12 hours, grind the dried Cu-ZnO solid into powder, and then calcine in a muffle furnace at 370°C for 1 hour to obtain catalyst Cu-ZnO oxide powder;
[0065] ⑤ Press and screen to obtain 40-mesh Cu-ZnO oxide particles.
[0066] S2: Weigh 2.22g of Sr2MgSi2O7:Eu 2+ ,Dy 3+ Fully disperse in 10 mL of anhydrous ethanol, add the Cu-ZnO oxide particles prepared in step S1, and soak for 2 h;
[0067] S3: The mixture was transferred to an oven and dried at 60°C. During the drying process, it was stirred every 30 minutes until it was completely dry, so that SMSOED was fully and evenly coated on the Cu-ZnO surface, and then calcined in a muffle furnace at 500°C for 2 hours.
[0068] S4: Finally, the reaction was reduced in a tube furnace at 500°C for 2h under a 10% H2-N2 atmosphere to obtain a CuO-ZnO / long afterglow catalyst, which was recorded as 0.6CZ / LP.
[0069] Comparative Example 1
[0070] This comparative example provides a Cu-ZnO catalyst, which is prepared as follows:
[0071] S1: Dissolve 5.44 g of Cu(NO3)2·3H2O and 2.97 g of Zn(NO3)2·6H2O in 75 mL of anhydrous ethanol and stir to obtain solution A;
[0072] S2: Dissolve 5.04 g of H2C2O4·2H2O in 75 mL of anhydrous ethanol and stir to obtain solution C;
[0073] S3: adding solution C dropwise to solution A, stirring was continued for 4 h at room temperature and aging was performed, after which the product was centrifuged and washed twice with anhydrous ethanol;
[0074] S4: drying in a drying oven at 105°C for 12 hours, grinding the dried Cu-ZnO catalyst solid into powder, and calcining in a muffle furnace at 370°C for 1 hour;
[0075] S5: Finally, the catalyst was reduced at 500°C for 2h in a tubular furnace under a 10% H2-N2 atmosphere to obtain a Cu-ZnO catalyst, which was denoted as CZ.
[0076] Comparative Example 2
[0077] This comparative example provides a long afterglow catalyst, and its preparation method comprises the following steps:
[0078] The commercial long afterglow material SMSOED was reduced alone in a tube furnace under a 10% H2-N2 atmosphere at 500°C for 2 h to prepare a long afterglow catalyst, denoted as L.
[0079] Experimental Example 1
[0080] 1 XRD characterization analysis of catalyst
[0081] In order to study the physical composition, crystallinity and particle size of the prepared catalysts CZ, 0.6CZ / LI, 0.6CZ / LP and L, XRD was used to characterize the results. Figure 1 shown.
[0082] Figure 1The XRD spectra of L, CZ, 0.6CZ / LI and 0.6CZ / LP catalysts show that monoclinic Cu has sharp and strong characteristic diffraction peaks at 2θ=43°(111), 2θ=50°(200), and 2θ=74°(220) (JCPDS No.04-0836). The peak at 43° is a characteristic peak of basic copper nitrate. During the calcination process, a CuO-ZnO solid solution is easily formed, which allows some spacing between Cu atoms and Zn atoms. This is one of the important precursors for the preparation of CO through the RWGS pathway in the CO2 hydrogenation reaction in Cu-based catalysts. The characteristic diffraction peaks of ZnO belonging to the hexagonal crystal can be observed at 2θ=31°(100), 2θ=34°(002) and 2θ=36°(101) (JCPDS No.36-1451). At the same time, no other impurity peaks were observed in the XRD diagram of CZ, proving that the CZ catalyst has a high purity. After the CuO-ZnO catalyst was loaded into the long afterglow material, it can be clearly observed that the diffraction peak intensity of Cu was weakened, which shows that the dispersion of the catalyst can be greatly increased after the long afterglow material is introduced into the CuO-ZnO catalyst. As shown in Table 1, the average particle size of Cu in the 0.6CZ / LI catalyst was 20.61nm, and the average particle size of Cu in the 0.6CZ / LP catalyst was 23.68nm, all of which were smaller than the average particle size of Cu in the CZ catalyst of 30.95nm. This also shows that after the CuO-ZnO catalyst was loaded into the long afterglow material, the crystallinity of Cu was effectively weakened and the dispersion of Cu was greatly promoted, but the average particle size of ZnO in the three catalysts was not much different. Through the XRD characterization analysis of commercial long afterglow materials, it is found that they have a Sr2MgSiO7 (JCPDS No.75-1736) crystal phase similar to the tetragonal system, which indicates that the long afterglow material will not introduce other impurity phases in the co-doped system with CuO-ZnO.
[0083] 2 BET characterization analysis of catalyst
[0084] The four catalysts CZ, 0.6CZ / LI, 0.6CZ / LP and L were subjected to N2 physical adsorption and desorption tests. The structural properties of the catalysts, specific surface area curves and pore size distribution curves were obtained through the adsorption and desorption isotherms. Figure 2 As shown. Figure 2 It can be seen that the pore structure of the long afterglow material will not be destroyed by the impregnation method.
[0085] Table 1 Physical properties of CZ, L, 0.6CZ / LI, 0.6CZ / LP catalysts
[0086]
[0087] 3 UV-vis characterization analysis of catalysts
[0088] In the photothermal catalytic reaction, the light absorption characteristics of the catalyst are the key factors affecting the photothermal catalytic performance. Therefore, this paper uses UV-vis absorption spectroscopy to characterize and test the light absorption ability of the catalyst. Figure 3 shown.
[0089] UV-vis absorption spectroscopy was used to characterize the light absorption capacity of the catalyst. Figure 3 It can be seen that the light absorption properties of the four catalysts are very different. First, the L catalyst has a strong absorption peak in the ultraviolet wavelength region (200nm~400nm), and its absorption edge is at 450nm, but there is no obvious absorption peak in the visible light wavelength region (400nm~800nm). The CZ catalyst also has no absorption peak in the visible light band. Its absorption peak in the ultraviolet region of 230nm~300nm wavelength is attributed to the electron oscillation generated by the absorption of visible light by Cu metal nanoparticles and the separation of photogenerated electron-hole pairs generated by the band gap of semiconductor ZnO under the excitation of the light source. By comparing with the other two catalysts in the visible light wavelength region, it can be seen from the figure that the two supported long afterglow catalysts prepared by different methods show considerable absorption peaks in the ultraviolet and visible light regions, and their light absorption properties gradually increase, and the absorption range of light extends from the ultraviolet band to the visible light band. The 0.6CZ / LI catalyst has a larger absorption peak in the wavelength range of 200-800nm, indicating that it has better light absorption properties (UV-Vis). The absorption peak shape of the 0.6CZ / LP catalyst to light is not as ideal as that of the 0.6CZ / LI catalyst, but it is also better than that of the L catalyst and the CZ catalyst. The above shows that the introduction of the long afterglow material may reduce the band gap of the catalyst material, which may be attributed to the fact that the doped ions in the long afterglow material introduce an intra-band state between the conduction band and the valence band of its matrix, resulting in a strong visible light absorption ability, thereby affecting its photothermal catalytic performance, which is also a typical defect state light absorption feature.
[0090] For semiconductor materials, band gap is an important parameter, which can be divided into direct band gap and indirect band gap. The band gap width is the energy difference between the conduction band and the valence band in semiconductor materials. The biggest difference between direct band gap and indirect band gap is that in the direct band gap, as long as the electron absorbs photons to change momentum during the transition, the transition may occur, while in the indirect band gap, not only the momentum needs to be absorbed during the transition, but also energy is needed to support the electron transition. The band gap width E of semiconductor catalysts is generally calculated by combining the UV-vis absorption spectrum using the Tauc plot method. g , and by Tacu formula (αhν) (1 / n) =A(hν-E g) to calculate whether it is a direct band gap. The band gap widths of the four catalysts CZ, L, 0.6CZ / LI and 0.6CZ / LP are as follows Figure 4 As shown, three points are taken from the position of the approximate straight line in the figure and connected. 2 For a linear relationship line segment above 0.99, extend the line segment to the horizontal coordinate to find the intersection point. The value of the intersection point is E g After calculation, we can get E g The band gaps of the four catalysts are 4.19eV, 2.77eV, 1.72eV, and 1.60eV, respectively. The band gaps of the four catalysts are all direct band gaps. The band gaps of the 0.6CZ / LI and 0.6CZ / LP catalysts are much smaller than those of the CZ and L catalysts. This indicates that the introduction of long afterglow can make it easier for the photogenerated electrons generated by the catalytic system under photoexcitation to jump from the conduction band to the valence band to participate in and promote the reduction of CO2, and leave more holes in the conduction band to participate in the dissociation of H2 to generate H + , improving catalytic performance.
[0091] 4 XPS characterization analysis of catalyst
[0092] The valence state of Cu is crucial for the CO2 hydrogenation reaction to CO. XPS characterization was used to determine the chemical state of Cu in the active center of Cu-containing catalysts. Figure 5 (a) shows the XPS spectra of Cu2p of CZ, 0.6CZ / LI and 0.6CZ / LP catalysts, where the peaks in the binding energy range of 952–955 eV correspond to Cu2p 1 / 2 orbital, the peak in the binding energy range of 932-935 eV corresponds to Cu2p 3 / 2 For the reduced catalyst, the characteristic peaks at 932 and 952 eV are attributed to Cu + or Cu 0 The characteristic peaks at 935 and 955 eV are attributed to Cu 2+ The characteristic peak at 943 eV is attributed to Cu 2+ This indicates that the catalyst was not completely reduced during the reduction process, and there is still a part of Cu 2+ The figure also shows that the 0.6CZ / LI catalyst has 1 / 2 Orbital and Cu2p 3 / 2 The orbitals are enhanced by 0.22 eV compared to the CZ catalyst. This may be because the combination of the long afterglow material and Cu-ZnO makes it more difficult for electrons to escape from Cu-O, thus increasing the binding energy of Cu2p.
[0093] Since XPS has a low resolution for Cu elemental analysis and Cu + and Cu 0The binding energies of the reduced Cu species are similar in XPS spectra, and it is difficult to determine the Cu valence ratio using XPS. Therefore, in order to further analyze the valence state of Cu species in the catalyst, Cu LMM X-ray Auger electron spectroscopy (XAES) was used to further distinguish the Cu species on the surface of the reduced catalyst. + and Cu 0 The peak fitting results of Cu Auger spectrum are as follows: Figure 5 As shown in (b), the Auger energy of all catalysts can be decomposed into the peak at 916.8 eV attributed to Cu + , the peak at 918.6 eV is attributed to Cu 0 The Cu of CZ catalyst can be obtained by the peak area. + / Cu 0 The ratio is 0.73, 0.6CZ / LI catalyst Cu + / Cu 0 The ratio is 1.45, 0.6CZ / LP catalyst Cu + / Cu 0 The ratio is 1.14, which indicates that the 0.6CZ / LI catalyst has a higher Cu + In previous studies, the surface of Cu-based catalysts was + When Cu is the main component, the catalytic activity of the catalyst for CO2 can be improved. 0 It is more conducive to visible light absorption and promotes the dissociation of H2. The introduction of long afterglow materials not only improves the reduction performance of Cu and Cu + / Cu 0 The ratio also provides a more superior catalytic basis for the Cu-ZnO system, making the catalyst have stronger CO2 reduction performance.
[0094] Table 2 XPS analysis to determine the percentage of oxygen vacancies and lattice oxygen in the catalyst
[0095]
[0096] The XPS characterization results of Zn are as follows Figure 6 As shown in (a), the two peaks with binding energies of 1022.7 and 1045.9 eV correspond to the Zn2p3 / 2 and Zn2p1 / 2 orbital binding peaks, respectively, and the distance between the two peaks is 23 eV. 1 / 2 Orbital and Zn2p 3 / 2 Although the orbital is enhanced by 0.19eV and 0.15eV compared to the CZ catalyst, only the divalent peak due to spin-orbit splitting can be analyzed in the XPS spectrum of Zn, confirming that ZnO is the state in which the Zn component exists. Therefore, ZnO is the only form among these catalysts.
[0097] In the photothermal catalytic system, the Eg The decrease in v This is because O v The concentration of can change the Fermi level of the semiconductor and thus reduce E g Improve light absorption capacity, while O v It also affects CO2 adsorption. Figure 6 (b) shows the catalyst for O v The XPS characterization results of the CZ, L, 0.6CZ / LI and 0.6CZ / LP catalysts show that the O1s spectra can be fitted with two oxygen species, corresponding to O v and lattice oxygen (O 2- ), the XPS semi-quantitative analysis results shown in Table 2 are catalyst O v and O 2- Ratio, 0.6CZ / LI O v The ratio is 62.87%, which is higher than 57.18%, 50.89% and 53.81% of the other three catalyst samples, indicating that the preparation method of the present application can effectively load Cu-ZnO into the long afterglow material. At the same time, the addition of the long afterglow material promotes the generation of more O in 0.6CZ / LI. v , proving the effectiveness of the supported long afterglow catalyst in the reaction. In particular, by comparing Example 1 and Example 5, it can be seen that the oxygen vacancy (Ov) content of Example 1 is 62.87%, which is higher than that of Example 5 (53.81%). This is because the catalyst has more active sites (XPS results) by adopting the preparation method of Example 1. By comparing the O1s electron binding energies of L and 0.6CZ / LI, it can be seen that there is a significant difference. The binding energy of 0.6CZ / LI is 531.85eV, which is significantly lower than that of L at 532.29eV. The research results show that when an element loses its outer electrons with lower binding energy, the interaction force of the remaining outer electrons will increase, and the electron binding energy will increase. Therefore, the 0.6CZ / LI catalyst has a higher electron density, enhances electron enrichment, activates CO2 molecules, and promotes the absorption of visible light, making it easier for the sample to excite electrons under light.
[0098] The VB valence band of the catalyst was determined by XPS valence band spectrum analysis, and the results are as follows: Figure 7As shown, the VB of catalysts CZ, 0.6CZ / LI and 0.6CZ / LP are 0.88eV, 0.75eV and 1.47eV, respectively. According to calculations, the conduction bands (CB) of the catalysts are -3.31eV, -0.97eV and -0.13eV, respectively. The reduction potentials of the three samples are all negative to the CO2 / CO reduction potential (-0.52eV), so the electrons generated under light can selectively promote the CO2 reduction reaction. Since the CB value of 0.6CZ / LI is 0.97eV, which is closer to the CO2 / CO reduction potential of 0.52eV, the electrons generated by the 0.6CZ / LI catalyst have more suitable energy than other catalysts, and are more conducive to promoting the generation of the target product CO under light.
[0099] 5 H2-TPR characterization analysis of catalysts
[0100] The reducibility of the active components of the catalyst has a great influence on the mechanism and performance of the RWGS reaction. Therefore, in order to explore the difficulty of the long afterglow material on the reduction performance of the Cu-based catalyst and the hydrogen consumption, the catalyst was characterized by H2-TPR. The results are as follows: Figure 8As shown. From the H2-TPR curve, it can be seen that except for the L catalyst which is difficult to be reduced in the entire temperature range, the remaining three catalysts have only one reduction peak, which is the hydrogen reduction peak of CuO, which indicates that the active component of the catalyst, CuO, exists in a single state in the system. In the characterization results, the CZ catalyst began to be slowly reduced at 190°C, reached a maximum value at 280°C, and ended at 330°C; the 0.6CZ / LI catalyst began to be slowly reduced at 140°C, reached a maximum value at 252°C, and ended at 296°C; the 0.6CZ / LP catalyst began to be slowly reduced at 157°C, reached a maximum value at 256°C, and ended at 300°C. The reduction temperature of pure CuO in a hydrogen atmosphere is usually between 200 and 300°C, and the reduction temperature of ZnO is generally in the range of 400 to 600°C, but no reduction peak of ZnO was found in the figure, indicating that ZnO exists in a relatively stable structure in the catalyst system, which is consistent with the XPS results. The reduction temperatures of the three catalysts are 0.6CZ / LI<0.6CZ / LP<CZ, and the reduction temperature of Cu-Zn / long afterglow after loading is lower, indicating that the interaction between the long afterglow material and Cu-ZnO will promote the dispersion of Cu, and by increasing the existence state of Cu species in the catalyst, make it easier to reduce. At the same time, the smaller the Cu grain size, the easier it will be reduced. Therefore, the comprehensive characterization results show that the Cu grain size in 0.6CZ / LI is the smallest and the Cu size of the CZ catalyst is the largest, which is consistent with the XRD characterization results. It can also be seen from the figure that the relationship between the reduction peak areas of the three is still 0.6CZ / LI<0.6CZ / LP<CZ, which shows that the introduction of long afterglow materials can increase the content of the active component CuO and form more Cu + or Cu 0 to promote the reduction of CO2.
[0101] 6. CO2-TPD Characterization Analysis of Catalysts
[0102] from Fig. 9 It can be seen from the CO2-TPD curves of different catalysts that the main CO2 adsorption peak in the experiment appears between 150 and 250°C. First, the L catalyst does not show an adsorption effect on CO2 in the entire temperature range. The CZ catalyst has a CO2 adsorption peak with a peak value of 183°C at the weak alkaline site of 70 to 200°C, while the 0.6CZ / LI catalyst shows a wide peak range for CO2 adsorption from 187°C to 243°C corresponding to the strong alkaline adsorption site. When the long afterglow material is introduced into the Cu-ZnO system, it can be seen that the adsorption peak, area and position of CO2 in the low and high temperature zones are increased, indicating that the combination of the two can increase the number and strength of alkaline sites, thereby improving the adsorption of acidic CO2.
[0103] 7. Catalyst reaction performance evaluation
[0104] (1) Selection of experimental conditions
[0105] The catalytic performance evaluation of CO2 hydrogenation reaction was carried out on an intermittent reactor. Before the reaction test, 0.1g of the reduced catalyst was placed in an intermittent reactor. After sealing, 3MPa of CO2 was filled into the reactor to test the air tightness of the device for 30 minutes. After passing the test, CO2 was repeatedly evacuated 3 times to make sure that there was no other gas in the reactor.
[0106] In order to distinguish the reaction performance of the supported long afterglow catalyst under different pressures, H2 and CO2 were introduced into the reactor at a ratio of 3:1 to 1, 2, and 3 MPa to explore the selectivity of the catalyst for CO2 hydrogenation reduction products. The reaction time was 4h, the reaction temperature was 240℃, and the catalyst dosage was 0.1g. After the reaction, the products CO and CH3OH were analyzed and detected.
[0107] The chromatographic detection method is a conventional chromatographic detection method, which is as follows: the reaction device is connected to the chromatograph, and the gas phase product after the reaction is completed is passed into the SP9650 gas chromatograph equipped with TCD for analysis, and the peak areas of H2, CO2 and CO are recorded at the same time. After the detection of the meteorological product is completed, the remaining reaction product is cooled and collected through the cold well, and passed into the solvent CH3(CH2)3OH to absorb the gaseous CH3OH. After waiting for the gas in the reactor to be emptied, 1μL of the CH3(CH2)3OH and CH3OH mixture is injected into the SP6890 gas chromatograph equipped with FID detector for analysis using a sampling needle, and the peak areas of CH3(CH2)3OH and CH3OH are recorded. Qualitative analysis is performed through the retention time of each component, and finally the peak area is combined to ensure the accuracy of the analysis, and finally the selectivity of CO and CH3OH, CO2 conversion rate and other activity data are calculated. Both chromatographs use high-purity Ar as the carrier gas.
[0108] Select performance such as Fig.10 As shown in (a), with the increase of pressure, it can be observed that the selectivity of CO in both the light storage experiment group and the pure heat experiment group gradually decreases, while the selectivity of CH3OH gradually increases. This indicates that as the pressure increases, more CO continues to react with H2 to generate carboxyl groups, and then the carboxyl groups continue to react with H2 to form CH3OH, or CO2 directly activates H2 at the catalytic active site to react to obtain the intermediate product formate, and then continues to add H2 to convert it into CH3OH. Therefore, 1MPa was selected as the reaction pressure for subsequent experiments.
[0109] pass Fig.10As shown in (b), the effect of catalysts on product selectivity in CO2 hydrogenation catalytic reactions can be observed in different temperature ranges. First, at 220°C, the selectivity of CZ catalyst and 0.6CZ / LI catalyst for CO was 69.7% and 94.8%, respectively. As the temperature increased to 240°C, the selectivity of the two catalysts for product CO was maintained between 92-94% and 97-98%. As the temperature increased, the selectivity of the by-product CH3OH decreased significantly, which is in line with the laws of thermodynamics. This shows that the 0.6CZ / LI catalyst has good RWGS activity.
[0110] (2) Catalytic performance evaluation
[0111] In the catalytic reaction, H2 and CO2 were introduced into the reactor in a ratio of 3:1 to 1MPa, the catalyst dosage was 0.1g, and the reaction was carried out at 240℃ for 4h. The performance of seven catalysts, CZ, L, 0.3CZ / LI, 0.6CZ / LI, 1.2CZ / LI, 1.8CZ / LI, and 0.6CZ / LP, in catalyzing the hydrogenation of CO2 to CO was compared. In particular, due to the introduction of long afterglow materials, the 0.6CZ / LI and 0.6CZ / LP catalysts acquired special light storage properties. After irradiation with a Xe lamp (CEL-PF300-T8) as a light source (power of 300W) for 5min, they still had considerable catalytic performance without the aid of a light source.
[0112] like Fig.11 The figure shows the changes in CO selectivity and yield and CO2 conversion rate and conversion rate in the catalytic reaction. Fig.11 (a) shows that the L catalyst cannot convert CO2 to CO, the selectivity of CZ catalyst to CO2 is 87.04%, the selectivity of 0.3CZ / LI, 0.6CZ / LI, 1.2CZ / LI and 1.8CZ / LI catalysts to CO in the catalytic reaction is 89.11%, 98.35%, 97.99%, 97.97%, respectively, the selectivity of 0.6CZ / LP catalyst to CO is 95.02%, and the selectivity of CZ / LI system to CO is almost higher than that of CZ and 0.6CZ / LP catalysts. At the same time, the CO yield is compared, and the CO yield of CZ catalyst in the reaction is 1727.05μmol·g -1 ·h -1, the CO yields of 0.6CZ / LI, 1.2CZ / LI and 1.8CZ / LI catalysts were 7 times, 3.10 times and 2.78 times higher than those of the CZ catalyst, respectively. The CO yield of the 0.6CZ / LP catalyst was 3.35 times that of the CZ catalyst. It is reported that the effect of Cu-based catalysts on CO conversion is mainly determined by the state of Cu. More specifically, highly dispersed Cu, large metal surface area and small metal particle size are more conducive to obtaining higher catalytic activity. The selectivity of CO shows a gradual upward and stable trend with the increase of long afterglow loading. This may be because the long afterglow material increases the dispersion of the active component Cu, enhances the LSPR effect of Cu and thus increases the absorption of visible light, which is consistent with the results of XRD, N2O titration and UV-vis absorption spectroscopy characterization. Fig.11 By comparing the CO2 conversion rate and the conversion rate in (b), it can be concluded that the L catalyst has no activity for the reduction catalysis of CO2. The CO2 conversion rate of the CZ catalyst is the lowest, only 4.36%. The CO2 conversion rates of the 0.6CZ / LI, 1.2CZ / LI and 1.8CZ / LI catalysts are 2.22 times, 1.30 times and 1.09 times higher than those of the CZ catalyst, respectively. The CO2 conversion rate of the 0.6CZ / LP catalyst is 1.44 times that of the CZ catalyst. The CO2 conversion rate of the CZ catalyst is 1948.79 μmol·g -1 ·h -1 The CO2 conversion rates of 0.6CZ / LI, 1.2CZ / LI, 1.8CZ / LI and 0.6CZ / LP catalysts were 6.62 times, 2.81 times, 2.62 times and 3.13 times higher than those of CZ catalyst, respectively. The comparative tests of the above samples show that the introduction of long afterglow makes 0.6CZ / LI catalyst produce more Cu + And improve O v concentration, giving it better CO2 adsorption capacity and higher catalytic activity.
[0113] (3) Reaction kinetics test
[0114] In order to explore the contribution of long afterglow materials in the CO2 hydrogenation reaction system, the catalytic performance of 0.6CZ / LI and CZ catalysts at different temperatures was compared. Fig.12 , 13 The Arrhenius equation is used to draw the catalytic performance and reaction temperature curve to explore the effect of long afterglow materials on the reaction activation energy. The results show that the E a 62.30 kJ·mol -1 , E of CZ catalyst a 111.36 kJ·mol -1It can be seen that after Cu-ZnO is loaded into the long afterglow material, the activation energy decreases by 49.06 kJ·mol -1 This may be because the hot electrons excited by the long afterglow material promote the activation of the product, which can reduce the reaction energy barrier for reducing CO2 to CO and improve the selectivity of CO.
[0115] (4) Stability test
[0116] Fig.14 The relationship between the selectivity of CO and the conversion rate of CO2 over time in the CO2 hydrogenation reaction of 0.6CZ / LI catalyst is shown. It can be seen that the selectivity of CO in the reaction approaches equilibrium after 4 hours, and the conversion rate of CO2 is close to stability after 7 hours.
[0117] This application uses the impregnation method to load Cu-ZnO catalyst onto long afterglow material to prepare a photothermal synergistic catalyst for CO2 hydrogenation to produce CO, and compares it with CuO-ZnO catalyst. Comparative studies have found that 0.6CZ / LI has the most outstanding catalytic performance. The analysis and characterization results clarify the mechanism of action of each active component of 0.6CZ / LI in the photothermal catalytic system:
[0118] 1. Compared with CZ catalyst (CO selectivity 89.11%, conversion rate 1727.05 μmol·g -1 ·h -1 ), the performance of 0.6CZ / LI catalyst has higher CO selectivity (98.35%) and conversion rate (12085.65 μmol·g -1 ·h -1 ). At the same time, the long afterglow material acts as a light source in the 0.6CZ / LI catalyst system and provides more O v This not only makes the 0.6CZ / LI catalyst have better light absorption performance, but also enhances the catalyst's adsorption capacity and catalytic activity for CO2.
[0119] 2. By analyzing the characterization results of BET and N2O titration, it can be clearly seen that all three catalysts are H3 type hysteresis loops and belong to mesoporous structures. By calculating the particle size and dispersion of Cu, it can be seen that the introduction of long afterglow materials changes the particle size and dispersion of Cu. The particle size decreases from 31nm to 20.6nm, and the dispersion increases from 0.89% to 10.27%, which is consistent with the XRD analysis.
[0120] 3. Through the analysis of the valence states of Cu, Zn and O, the 0.6CZ / LI catalyst has a higher Cu dispersion and a higher proportion of Cu + / Cu 0 Ratio. 0.6CZ / LI catalyst Cu + / Cu0 The ratio is 1.45, which is more than the Cu of CZ catalyst. + / Cu 0 ratio (0.73), in previous studies Cu + It can enhance the adsorption of CO2, improve the hydrogenation of CO2 and reduce it to CO. This result proves that the long afterglow material can regulate the number of active components. At the same time, only the divalent peak caused by Zn spin orbit splitting can be observed in the two catalysts, which shows that ZnO is the only form in the catalyst system. From the XPS characterization analysis of O1s, it can be seen that the Ov concentration of 0.6CZ / LI catalyst is higher than that of CZ and long afterglow catalysts, which shows that the introduction of long afterglow can effectively increase the Ov content. The main role of Ov in the catalytic system is to enhance the electron enrichment effect, activate CO2 molecules, and promote the absorption of visible light, making it easier for the catalyst to excite electrons under light.
[0121] The embodiments of the present application are described above in conjunction with the accompanying drawings, but the present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.
Claims
1. A supported Cu-ZnO / long afterglow catalyst, characterized in that: The method uses a long afterglow material as a carrier and loads Cu-ZnO active components on the surface of the long afterglow material through an impregnation method.
2. The supported Cu-ZnO / long afterglow catalyst according to claim 1, characterized in that: The long afterglow material is Sr2MgSi2O7:Eu 2+ ,Dy 3+ .
3. The supported Cu-ZnO / long afterglow catalyst according to claim 1 or 2, characterized in that: The raw materials for preparing the active component are soluble copper salt and soluble zinc salt, and the molar ratio of Cu to Zn is 1-9:
1.
4. The supported Cu-ZnO / long afterglow catalyst according to claim 3, characterized in that: The molar ratio of the active component Cu to Si in the long afterglow material is 0.3-1.8:
1.
5. The supported Cu-ZnO / long afterglow catalyst according to claim 3, characterized in that: The soluble copper salt is Cu(NO3)2, and the soluble zinc salt is Zn(NO3)2.
6. The method for preparing the supported Cu-ZnO / long afterglow catalyst according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: dissolving soluble copper salt and soluble zinc salt in anhydrous ethanol, stirring well to obtain solution A; S2: Add the long afterglow material to solution A and continue stirring to obtain solution B; S3: dissolving oxalic acid in anhydrous ethanol and stirring to obtain solution C; S4: Slowly and evenly add solution C to solution B, and continue stirring at room temperature for 0.5-6 hours to obtain a gel precipitate. After aging at room temperature, the product is centrifuged and washed with anhydrous ethanol 2-3 times. S5: Place the catalyst in a drying oven at 80-120°C and dry for 8-24 hours, grind the dried catalyst solid into powder, and then calcine it in a muffle furnace at 300-500°C for 0.5-5 hours; S6: Reduce in a tube furnace at 300-500°C for 1-3h under 10% H2-N2 atmosphere to obtain a supported Cu-ZnO / long afterglow catalyst.
7. The method for preparing the supported Cu-ZnO / long afterglow catalyst according to claim 6, characterized in that: In step S1, the molar ratio of Cu to anhydrous ethanol is 0.01-0.2:1, preferably 0.0175:1; in step S3, the molar ratio of oxalic acid to anhydrous ethanol is 0.01-0.2:
1.
8. The method for preparing the supported Cu-ZnO / long afterglow catalyst according to claim 6, characterized in that: The molar ratio of Cu to oxalic acid is 0.1-5:
1.
9. Use of the catalyst according to any one of claims 1 to 5 in the preparation of CO by photothermal catalytic reduction of CO2 hydrogenation.
10. The use according to claim 9, characterized in that: The CO2 hydrogenation photothermal catalytic reduction to prepare CO is carried out in an intermittent reactor, and H2 is introduced into the intermittent reactor at a ratio of 3:
1. and CO2 to a pressure of 0.5-4 MPa, and the amount of the supported Cu-ZnO / long afterglow catalyst used is 0.05-0.2 g.